A Note on Measuring the Share of the Public Sector - Marris, R. (Review of Economic Studies, 1954)
Journal Article A Note on Measuring the Share of the Public Sector Get access R. Marris R. Marris Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 3, 1954, Pages 214–219, https://doi.org/10.2307/2295878 Published: 01 January 1954